Vestibular dysfunction in Parkinson’s disease: a neglected topic - Gui, Meilin; Lv, Lingling; Qin, Lixia; Wang, Chunyu (Frontiers in Neurology, 2024)
Dizziness and postural instability are frequently observed symptoms in patient with Parkinson’s disease (PD), potentially linked to vestibular dysfunction. Despite their significant impact on quality of life, these symptoms are often overlooked and undertreated in clinical practice. This review aims to summarize symptoms associated with vestibular dysfunction in patients with PD and discusses vestibular-targeted therapies for managing non-specific dizziness and related symptoms. We conducted searches in PubMed and Web of Science using keywords related to vestibular dysfunction, Parkinson’s disease, dizziness, and postural instability, alongside the reference lists of relevant articles. The available evidence suggests the prevalence of vestibular dysfunction-related symptoms in patients with PD and supports the idea that vestibular-targeted therapies may be effective in improving PD symptoms.